Ilakkiyattil vēḷāṇmaik kalaiccoṟkaḷ - Kandasamy, L. S., 1939-; Jayaraman, Nannilam Veerappa, 1934- (Tamiḷnāṭu Vēḷāṇmaip Palkalaikkaḷakam, 1981)
Glossary of agricultural terms gleaned from Eṭṭuttokai and Pattuppāṭṭu, Sangam anthologies.